Experimental and computational analysis of piezoelectrically excited vibrating tools. (2017) - Holl, H.J.; Meindlhumer, M.; Simader, V.; Brandl, A.; Edelbauer, R.; Ehrentraut, M.; Baldinger, M.
Abstract: The reduction of the cutting forces in agricultural machines is important and frequently vibrating cutting tools are considered. In this contribution piezoelectric excitations are analyzed with respect to their effectiveness and various piezoelectric actors are used in the experimental setup, like piezo-stack, piezo-patch, which act directly at the cutting tool. Transversal and longitudinal vibration directions are analyzed with respect to the cutting speed direction. A suitable mechanical model has been implemented in ANSYS and the eigenfrequency analysis shows the important parameters. For various frequencies piezoelectric excitations have been studied in the considered frequency range. The experiments confirmed the results of the friction model that the ratio of the vibration speed of the cutting tool and the cutting speed is important and determines the resulting cutting force.